ELLEN G. WHITE PERSPECTIVE ON POLITICS AMONG SEVENTH DAY ADVENTIST LEADERS - Lumingkewas, Edwin Melky (Klabat Theological Review, 2021)
Politics is taking place into pastoral leadership. This practice has its chance to be practiced because of cultural background. However, it brings contention among pastors and affect the mission of the church. Ellen G. White as one of the founder of SDA church paid attention to the practice of politics in the church. For SDA church members politics is restricted because it brings evil effects unto physical, mental and spiritual life. They need to avoid politics in order to develop true God’s character. It can also create division among church members. And the most important is if Christians cling into it, God would not acknowledge them as His people. For pastors and teachers, their role is to form the mindset of church members. This role prohibits them to politics.  They will not bring unity in the church when they involve politics in their discourses. Even in more firm statement Ellen White ask them to be disqualified from work which paid by tithe. While He was on the earth, Jesus never practice politics. So every Christian need to be away from politics.   Keywords: Politics   References Allen, Robert W, Dan L. Madison, Lyman W. Porter, Patricia A. Renwick, and Bronston T. Mayes, “Organizational Politics: Tactics and Characteristics of Its Actors. California Management Review 22, 1979. Cervero, Ronald M. and Arthur L. Wilson, Planning Responsibly in Adult Education: A Guide to Negotiating Power and Interests . San Francisco: Jossey-Bass, 1994. Champoux, Joseph E. Champoux, Organizational Behavior: Essential Tenets for A New Millenium . Canada: Southwestern College, 2000. Champoux, Joseph E.   Organizational Behavior: Essential Tenets for A New Millenium . Canada: Southwestern College, 2000. Coopey, John and John Bourgoyne. “Politics and Organizational Learning.” Journal of Management Studies 37(6), (2000): 869-885. Forrester, Duncan B, Theology and Politics . New York: Basil Blackwell, 1988 French, Wendell and Cecil H. Bell, Organization Development: Behavioral Science Interventions for Organization Improvement . Englewood Cliffs, NJ: Prentice Hall, 1999. Gangel, Kenneth O, The Meaning of Leadership . In J. D. Berkley, Leadership handbook of management and administration (pp. 177-183). Manila, Philippines: CLC, 2007. Hitt, Michael A, Chet C. Miller, and Adrienne Colella, Organizational Behavior: A Strategic Approach . Hoboken, NJ: John Wiley & Sons, 2006. Kanter M. Rosabeth, Barry A. Stein, and Todd Jick, The Challenge of Organizational Change:How Companies Experience It and Leaders Guide It . New York: The Free, 1992 Kotter, John P, A Force for Change: How Leadership Differs from Management . New York: Free Press, 1990. Maleke, Ray “ A Minahasa Local Theology ,” (September 2013): http://raymaleke.blogspot.com/2013/09/chapter-six_2634.html, accessed 13 May, 2014. Mamahit, http://mamahit.com/ukung.html, (1994).  Accessed May 11, 2014 Marcos, “ Keindahan Demokratisasi dan Toleransi Di Minahasa ,” http://www.marcos.my.id/view/keindahan-demokratisasi-dan-toleransi-di-minahasa.html, (2013) accessed May 11, 2014 McCroskey, James, Virginia P. Richmond, Timothy Plax and Patricia Kearney, “Power in the Classroom: Behavior Alteration Techniques, Communication Training and Learning. Communication Education 34 (1995). McShane, Steven L and  Mary Ann Von Glinow, Organizational Behavior 4th ed. New York: McGraw-Hill, 2008. Mintzberg, Henry, Mel Didier, and Gerry Arbic, Power in and Around Organizations Englewood Cliffs, NJ: Prentice-Hall, 1983. Morgan, Gareth. Images of Organization. Thousand Oaks: Sage Publications, 2006. Paulin, Jon, “Politics in the church,” Ministry , August 2011, pp. 15-17. Pfeffer, Jeffrey, Managing with power: Politics and Influence in Organizations . Boston: Harvard Business School, 1993. Plax, Timothy, Patricia Kearney, and Timothy M. Downs, “Communicating Control in the Classroom and Satisfaction with Teaching and Students” Communication Education 35, 1986. Rahim, Afzalur M, “Relationship of Leader Power to Compliance and Satisfaction with Supervision: Evidence from A National Sample of Managers” Journal of Management 15, 1989. Roderick, “ The Minahasa: Si Tou Timou Tumou Tou ,” (2007), http://www.theminahasa.net/indexen.html.  accessed May 13, 2014 Senge, Peter M, The Fifth Discipline: The Art and Practice of the Learning Organization . New York: Doubleday/Currency, 2006. Siwi, Ramly “Masyarakat Minahasa Kuno, (2008), https://publikreport.com/ masyarakat-minahasa-kuno/, accessed 8 May 2021 Stott, John, Calling Christian Leaders: Biblical Model of Church, Gospel and Ministry . England: InterVarsity, 2002. Testimonies for the Church 7:252. SPCCSR 113.1 https://m.egwwritings.org/en/book/721.640#644 Wheatley, Margaret J, Leadership and the New Science: Discovering Order in A Chaotic World. San Francisco: Berrett-Koehler, 1992. White, Ellen G. (1855a; 2002), Testimonies for the Church, Vol. 4. Mountain View, CA: Pacific Press. White, Ellen G. Christian Service . Washington, DC: Review and Herald, 1925; 2002. White, Ellen G. Daniel an Example of Faithfulness, The Signs of the Times . Vol. 12.  Oakland, CA: International Tract and Missionary Society, 1886; 2002. White, Ellen G. Fundamentals of Christian Education, Instruction for the Home, the School, and the Church; Fundamentals of Christian Education , Southern Publishing Association, 1923; 2002. White, Ellen G. Pastoral Ministry . Silver Spring, MD: General Conference of Seventh-day Adventists, Ministerial Association, 1995. White, Ellen G. Testimonies for the Church , Vol.5. Mountain View, CA: Pacific Press, 1855b; 2002 White, Ellen G. Testimonies for the Church , Vol.9. (Mountain View, CA: Pacific Press, 1855c; 2002. White, Ellen G. Testimonies to Ministers and Gospel Workers . Mountain View, CA: Pacific Press, 1923; 2002. White, Ellen G., Testimonies to Ministers and Gospel Workers. (Mountain View, CA: Pacific Press, 1923; 2002). White, Ellen G., The Story of Prophets and Kings. (Mountain View, CA: Pacific Press, 1943). Yukl, Gary, Helen Kim, and Cecilia M. Falbe, “Antecedents Of Influence Outcomes” Journal of Applied Psychology 81, 1996.